2015
DOI: 10.4103/2277-9175.161537
|View full text |Cite
|
Sign up to set email alerts
|

Can we define severity of carpal tunnel syndrome by ultrasound?

Abstract: Background:Carpal tunnel syndrome (CTS) is a common entrapment neuropathy. Diagnosis of CTS is usually based on a combination of clinical symptoms and electrodiagnostic study (EDS). Ultrasonography (US) also has been shown to be a useful diagnostic tool in CTS and is based on an increase in the median nerve cross-sectional area (CSA) at the level of the pisiform bone. In this study we assessed findings in US in correlation with severity of CTS.Materials and Method:This was a cross-sectional case-control study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The US to measure CSA of the median nerve at the wrist is a useful test to determine moderate and severe CTS. The results of the present study revealed a positive correlation between CSA and CTS severities (r s =0.56), which was similar to previous studies [ 15 16 20 ]. The study of Mhoon et al [ 20 ] and Moran et al [ 16 ] reported 0.52 and 0.61 of positive correlation, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The US to measure CSA of the median nerve at the wrist is a useful test to determine moderate and severe CTS. The results of the present study revealed a positive correlation between CSA and CTS severities (r s =0.56), which was similar to previous studies [ 15 16 20 ]. The study of Mhoon et al [ 20 ] and Moran et al [ 16 ] reported 0.52 and 0.61 of positive correlation, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Cutoff values of 9 or 10 mm 2 were suggested as single diagnostic criterion in most previous studies [ 4 10 11 12 13 14 ]. Interestingly, several studies reveal that there is a positive correlation between the median nerve CSA and electrophysiological severities of CTS [ 15 16 ]. However, no well-designed study has been conducted for diagnosis of electrophysiologically moderate and severe CTS, which are to be considered for surgical treatment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two-point discrimination test and atrophy of the thenar musculature used in the CTS-6 model are directly linked to the severity of CTS [ 34 ]. A value of > 13 mm2 for the median nerve area found during US would correspond to a moderate degree of impairment [ 35 , 36 ]. Absence of a sensory response and abnormal distal motor latency during NCS would correspond to a severe degree of impairment [ 3 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography may be useful as an alternative diagnostic examination, especially as it can be employed more quickly than MRI [ 7 , 8 ]. However, the clinical efficacy and diagnostic reliability of ultrasonography in carpal tunnel syndrome has not yet been established and further studies are needed.…”
Section: Discussionmentioning
confidence: 99%